ANALYSIS OF LOW SELF-CONFIDENCE IN CLASS VI STUDENTS AT SD MARDI YUANA SERANG - Farhan Oktavian (STKIP Subang, 2022)
Education is very important in human life. Because education allows humans to know their abilities and potential. In an education there are 6 characters that must be developed, one of which is the character of self-confidence. Therefore, this study aims to determine the development of self-confidence in social studies learning, especially grade 6 at SD Mardi Yuana Serang. This study uses descriptive qualitative with the subjects in this study are teachers and students of SD Mardi Yuana Serang. Data collection techniques in this study used observation, interviews and documentation techniques. The results of this study indicate that the learning activities at SD Mardi Yuana have a much better improvement than before after using the cooperative learning method.